2018
DOI: 10.31000/prima.v2i2.707
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Keteraturan Matematis Pada Budaya Banten

Abstract: This research is motivated by the searching of banten cultural information which is viewed from mathematics aspect is still unfocus, whereas the culture contains the elements of mathematics, mathematics is the construction of the culture. The search for mathematical regularity in Banten culture can be a study that can be integrated in mathematics learning on transformation material. The research use descriptive qualitative research. Based on the results of research, on the object of Banten gate, Banten Great M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
0
0
5
Order By: Relevance
“…Haris and Putri (2011) explained that woven is suitable for the transformation geometry of mathematical concepts. This is in line with the results of several studies that demonstrated the motifs of woven can be used as a starting point in learning transformation (Fauzi & Setiawan, 2020;Khaerunnisa, Setiani, & Rafianti, 2018). On the other hand, the motifs of Bamboo woven have been successfully implemented in improving students' understanding of the concept of translation and rotation in transformation geometry (Maryati & Prahmana, 2020a;2020b).…”
Section: Introductionsupporting
confidence: 80%
“…Haris and Putri (2011) explained that woven is suitable for the transformation geometry of mathematical concepts. This is in line with the results of several studies that demonstrated the motifs of woven can be used as a starting point in learning transformation (Fauzi & Setiawan, 2020;Khaerunnisa, Setiani, & Rafianti, 2018). On the other hand, the motifs of Bamboo woven have been successfully implemented in improving students' understanding of the concept of translation and rotation in transformation geometry (Maryati & Prahmana, 2020a;2020b).…”
Section: Introductionsupporting
confidence: 80%
“…Pendidikan merupakan salah satu sektor pembangunan nasional yang didalamnya terdapat upaya mencerdaskan kehidupan bangsa untuk menghasilkan manusia yang berkualitas dan berwawasan luas. Adapun budaya atau kebudayaan dapat diartikan sebagai hasil kegiatan dari penciptaan akal budi, pikiran, dan adat istiadat manusia (Khaerunnisa et al, 2018).…”
Section: Pendahuluanunclassified
“…Wujud kebudayaan menurut Khaerunnisa et al, (2018) dibedakan menjadi tiga bagian, yaitu: (1) Gagasan, kebudayaan yang berbentuk kumpulan ide-ide atau gagasan bersifat abstrak dan tidak dapat disentuh atau diraba; (2) Aktivitas, kebudayaan dengan bentuk sebuah tindakan berpola dari manusia dalam bermasyarakat; dan (3) Artefak, kebudayaan dengan wujud fisik berupa hasil karya atau penciptaan manusia berupa benda-benda yang konkret dan dapat diraba.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations